Budaya Sabung Ayam: Studi Nilai Modal Kehidupan Masyarakat Balusu Bangunlipu Kabupaten Toraja Utara - Novelia Agnesia Palette'; Abdul Rahman (Rayhan Intermedia, 2023)
This research aims to determine the meaning of moral values in cockfighting culture, to examine forms of application of moral values of cockfighting culture in everyday life and to elaborate on society's views on the shift in cockfighting cultural values. To achieve this goal, qualitative research methods were used by means of observation, interviews and documentation. The data obtained is then analyzed and interpreted based on theory and relevant research results. The results of this research show that the preservation of cockfighting culture still exists today because some people make it a hobby, and it contains useful values. Cockfighting has become part of culture and for society, moral values are very important and influence life, therefore moral values need to be preserved to maintain harmony in society by understanding moral values, then applying them wherever they are and understanding society's views on changes. Moral values in cockfighting culture. To maintain the existence of these moral values, cockfighting culture will continue to be implemented.